Pengaruh Penggunaan Boost Konverter Sebagai Pengatur Tegangan Terhadap Daya Keluaran Sistem Plts 1.5 Kw - Aldifa Amendra Makruf; Andi M. Nur Putra; Sepannur bandri (Elkom: Jurnal Elektronika dan Komputer, 2024)
Utilization of new renewable energy is a solution to meet the increasing electricity demand, one of which is solar power generation technology. Solar panels are a renewable power generator that is environmentally friendly. The relatively low and unstable output voltage of PV is affected by solar irradiation, which becomes a constraint. Therefore, by utilizing a boost converter, the solar panel system is able to work 25% more optimally compared to without using a boost converter. The performance of solar panels when using a boost converter is around 83.3% and without using it, the performance is only about 58.3%. The average output power when using the boost converter is 1,521 W, whereas without using the boost converter, the average output power is 1,172 W. This indicates that the output power is more stable when using the boost converter compared to not using it. This research focuses on a boost converter with PID control as a support, optimizer, and voltage stabilizer where the output power on the solar panel is expected to be more optimal and the output from the solar panel is more stable with more optimal results in various conditions. In this study, 12 solar panels of 125 WP with a capacity of 1.5 KW are used in series-parallel to obtain the required power. If the output from the solar panel is insufficient due to weather conditions, the voltage will be increased by the boost converter towards the inverter so that the voltage remains stable into the inverter with the boost converter. This boost converter uses PID control to keep the output voltage stable.